Pengaruh Penggunaan Mobile Banking terhadap Kepuasan Nasabah Bank Syariah Indonesia Cabang Jambi - Abdul Gani; Putri Apria Ningsih; Ahmad Syahrizal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to reveal the effect of using mobile banking on customer satisfaction at Bank Syariah Indonesia Jambi Branch. This thesis uses a quantitative approach using a simple partial regression statistical analysis method with a sample of 68 customers. The results of the study show that there is a significant influence on the mobile banking usage variable (X) on customer decisions. with the tcount value on the mobile banking usage variable (X) amounting to 12,944 with a significance level of 0,000. Because the value of tcount is greater than ttable (12,944 > 2,387) and a significance value of 0.00 <0.05, Ho is rejected and Ha is accepted. Then the mobile banking usage variable (X) partially has a significant influence on customer decisions in using Bank Syariah Indonesia Mobile Banking Jambi Branch.